2012
DOI: 10.3415/vcot-11-11-0157
|View full text |Cite
|
Sign up to set email alerts
|

Dual mobility canine total hip prosthesis: Implant characteristics and surgical procedure

Abstract: Prosthetic dislocation is one of the most common complications after canine hip replacement. The use of dual mobility acetabular components has been shown to reduce the rate of dislocation in first intent hip replacement in human patients who are at high risk for dislocation. In such implants, a mobile polyethylene liner articulates on one side with a metallic acetabular component and on the other side with a metallic prosthetic head. A dual mobility cemented acetabular component has been designed for use in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[16][17][18] In the veterinary field, the only documented use of a DM cup is reported by Guillaumot and colleagues. 19,20 In his second publication, a cemented DM cup prosthesis was implanted in dogs, and no dislocation was experienced in 50 consecutive cases. 20 The overall rate of dislocation following a THA depends on several aspects, such as appropriate positioning of the implants, orientation and offset of the acetabular and femoral implants and the preservation of the local soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In the veterinary field, the only documented use of a DM cup is reported by Guillaumot and colleagues. 19,20 In his second publication, a cemented DM cup prosthesis was implanted in dogs, and no dislocation was experienced in 50 consecutive cases. 20 The overall rate of dislocation following a THA depends on several aspects, such as appropriate positioning of the implants, orientation and offset of the acetabular and femoral implants and the preservation of the local soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the ALO reduction results of DPO (À11 ) and TPO (À23 ), the choice of technique could be determined by the ALO at the time of luxation. 12 The aim would be to reach the recommended values (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) ). However, it has been seen previously that these values alone are not sufficient to prevent a recurrence of luxation.…”
Section: Discussionmentioning
confidence: 99%
“…Dual mobility cups have also been of major interest in humans, and studies in dogs suggested that they were effective in preventing luxation. 4,6,[38][39][40] These hypothetical recommendations should be investigated in future studies of THR luxations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation